Low-cost triboelectric nanogenerator based on aseptic carton package - Moreira, Kelly S.; Santos da Campo, Yan A.; Lorenzett, Ezequiel; Burgo, Thiago A.L. [UNESP] (Elsevier, 2023)
Triboelectric nanogenerators (TENGs) are efficient systems that convert mechanical energy to electrical energy. Based on contact electrification, an emerging powerful tool in energy harvesting technologies, most TENGs are constructed using expensive materials (e.g. gold and platinum) and costly processes. Aseptic carton packages (ACP) are plastic-laminated materials basically composed of paperboard, polyethylene and aluminum, but having all parts required for a TENG device: dielectric inductor and metal. Using the concept implicit in the triboelectric series where hydrophilic materials acquire a positive net charge while hydrophobic ones develop negative net charge upon contact, ACP was used as the main component of a sandwich-type triboelectric nanogenerator (ACP-TENG). Electrostatic potential mapping confirmed that pristine polyethylene is a negative charge inductor while after its oxidation develops an excess positive charge. Potentials as high as 200 V are reached with ACP-TENG during mechanical loads, charging a 10 μF capacitor to 3.5 V in less than 10 min. Continuous open-circuit voltage of roughly 80 V is developed under pressure-relaxation cycles at 1.8 Hz, reaching an output peak current of ∼400 nA. The efficiency of ACP-TENG is comparable to nanoengineered devices, but costing only a fraction of them. We believe that the ACP-TENG reported here is a reliable way to construct low-cost energy harvesting devices and it can be used as an environmentally friendly destination/solution for food packaging.
Keywords: Aseptic carton package; Energy harvesting; Triboelectric nanogenerator; Triboelectricity